KELOMPOK SPIRITUAL SAKKHI DAN DAMPAKNYA TERHADAP KEHIDUPAN KEAGAMAAN DI INDONESIA (Studi Hindu Khrisna Di Asram Prahlada Bumi Manti Lampung) - Suhanah Suhanah (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This research is about “Sakkhi Spiritual Group and Its Impact on Religious Life in Indonesia” (Study of the Hindu Krishna in Asram Prahlada Earth Manti Lampung)” The problems in this research are as follows: 1) What is the basic teachings of Sakkhi?2) What is the doctrine that distinguishes between Sakkhi and Hinduism or Hindu Traditional (e.g., PHDI, Indonesia’s Association of Darma Hinduism)?3) Is the doctrine recognized by Hindus generally (PHDI)?4) What are the views of PHDI on Sakkhi?5) Does the existence of Sakkhi conflict with PHDI? The purposes of this study are to address the aforementioned problems. This study uses a qualitative approach with study case method. The results of the study conclude that: 1) The Principal Teachings of Sakkhi regard Lord Krishna as the supreme God and even higher than that of the Tri Murti. The ultimate source of Sakkhi teaching is the holy book of Bhagavad Gita and the book of Purana. Sakkhi principles of morality that must be executed by followers are as follows a) Do not eat meat, fish and eggs. b) Do not get drunk. c) Do not gamble d) Do not commit adultery. 2) The matter that distinguishes between Sakkhi with Hinduism in general are; a) a place of worship for Sakkhi is called Persembahyangan, while the common Hinduism places of worship are called Pure. b) Sakkhi, God is called Lord Krishna, while the common Hinduism God is called Brahman. 3) Doctrines of Sakkhi are admitted by common Hindus because they are still recognized as Hindus and admit that the Vedas are the scriptures of Hinduism. 4) PHDI protect the existence of Sakkhi as long as they can live together and not be exclusive. They do not disput the different concept of God and religious rituals. The important thing is that Sakkhi could assimilate in the celebration of Hinduism. 5) The existence of Sakkhi is not conflicted with PHDI because Sakkhi is part of the Hinduism and under the auspices of PHDI. They do not accentuate the differences that exist. Thus it is unlikely to spark any dispute.